Psychometrics of three Swedish physical pediatric item banks from the Patient-Reported Outcomes Measurement Information System (PROMIS)®: pain interference, fatigue, and physical activity - Frida Carlberg Rindestig; Marie Wiberg; John Eric Chaplin; Eva Henje; Inga Dennhag (SpringerOpen, 2021)
Abstract Background The Patient-Reported Outcomes Measurement Information System (PROMIS®) aims to provide self-reported item banks for several dimensions of physical, mental and social health. Here we investigate the psychometric properties of the Swedish pediatric versions of the Physical Health item banks for pain interference, fatigue and physical activity which can be used in school health care and other clinical pediatric settings. Physical health has been shown to be more important for teenagers' well-being than ever because of the link to several somatic and mental conditions. The item banks are not yet available in Sweden. Methods 12- to 19-year-old participants (n = 681) were recruited in public school settings, and at a child- and psychiatric outpatient clinic. Three one-factor models using CFA were performed to evaluate scale dimensionality. We analyzed monotonicity and local independence. The items were calibrated by fitting the graded response model. Differential Item analyses (DIF) for age, gender and language were calculated. Results As part of the three one-factor models, we found support that each item bank measures a unidimensional construct. No monotonicity or local dependence were found. We found that 11 items had significant lack of fit in the item response theory (IRT) analyses. The result also showed DIF for age (seven items) and language (nine items). However, the differences on item fits and effect sizes of McFadden were negligible. After considering the analytic results, graphical illustration, item content and clinical relevance we decided to keep all items in the item banks. Conclusions We translated and validated the U.S. PROMIS item banks pain interference, fatigue and physical activity into Swedish by applying CFA, IRT and DIF analyses. The results suggest adequacy of the translations in terms of their psychometrics. The questionnaires can be used in school health and other pediatric care. Future studies can be to use Computerized Adaptive Testing (CAT), which provide fewer but reliable items to the test person compared to classical testing.